Association between atmospheric particulate matter pollution during pregnancy and premature birth in China: a meta-analysis - Bingbing Guo; Xinye Jiang (Frontiers in Public Health)
ObjectiveThe impact of maternal exposure to outdoor particulate matter during pregnancy on preterm birth is still inconsistent, particularly under the unique atmospheric particulate matter pollution conditions in China, where the effects on preterm birth remain poorly understood. The study intends to evaluate the correlation between atmospheric particulate matter pollution (PM2.5 and PM10) during pregnancy and premature birth in China through a Meta-analysis.MethodsThe Chinese databases (CNKI and Wanfangdata), and the English databases (PubMed, Web of Science, and Embase) were searched to collect literature related to exposure to atmospheric particulate matter during pregnancy in China and premature birth. A Meta-analysis was conducted using Stata12.0 software.ResultsA total of 29 studies were included in this study (15 cross-sectional studies, 11 cohort studies, and 3 case–control studies), covering more than 30 provinces (municipalities directly under the Central Government) in China, with a total sample size of 9,283,110 people. The Meta-analysis results showed that the risk of premature birth with the OR value was 1.03 (95%CI:1.011.06) for exposure to PM2.5 in mid-pregnancy, 1.03 (95%CI:1.011.04) for exposure to PM2.5 in late pregnancy, 1.07 (95%CI:1.051.10) for exposure to PM2.5 throughout pregnancy, and 1.04 (95%CI:1.001.07) for exposure to PM10 throughout pregnancy. No correlation was found between exposure to atmospheric particulate matter at other times and the occurrence of premature birth.ConclusionAlthough our results indicate that exposure to atmospheric particulate matter during the second and third trimesters of pregnancy increases the risk of preterm birth among pregnant women in China, the association is relatively weak. Additionally, the results may be influenced by potential confounding factors. Therefore, further detailed research is needed to explore the relationship between particulate matter exposure and preterm birth or other adverse pregnancy outcomes.